American meditative lyrics - Hunt, Theodore Whitefield (Benson collection of hymnals and hymnology, 1896)
The spiritual element in poetry.--William Cullen Bryant.--Henry Wadsworth Longfellow.--Ralph Waldo Emerson.--Edgar Allan Poe.--John Greenleaf Whittier.--James Russell Lowell.--Bayard Taylor.--Oliver Wendell Holmes.--Mrs. Harriet Beecher Stowe.--American memorial lyrics: elegies.--American devotional lyrics: hymns.--Some later lyrists.